Peranan Modal Ventura sebagai Alternatif Pembiayaan Usaha Kecil dan Menengah - Safrina Safrina (Universitas Syiah Kuala, 2013)
ABSTRACT: The existence of venture capital in Indonesia cannot be separated from an idealism to develop small and medium businesses as a pillar of the economy. This paper aims to evaluate the role of venture capital as an alternative financial support for small and medium entrepreneurs, particularly the role of PT Sarana Aceh Ventura (PT SAV). This research applies a descriptive analysis method with a yuridis and empirical approached. The research findings are that there are many obstacles in the implementation process which resulted in the financing is still unfamiliar to small businesses, the unique characteristic of venture capital as an active investment that shows through mentoring is not applied and the form of small businesses in Indonesia that is mostly family business becomes problems when it is faced to an active investment that needed partnership between companies and businesses. The Role of Venture Capital as an Alternative Financial Support for Small And Medium Entrepreneurs